Therapy Response Evaluation of Malignant Lymphoma in a Multicenter Study: Comparison of Manual and Semiautomatic Measurements in CT - Weßling, J.; Schülke, C.; Koch, R.; Kohlhase, N.; Wassenaar, L.; Mesters, R.; Höink, A. J.; D´Anastasi, M.; Karpitschka, M.; Fabel, M.; Wulff, A. M.; Pinto dos Santos, D.; Kiessling, A.; Graser, A.; Bornemann, L.; Dicken, V.; Heindel, W.; Buerke, B. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Comparison of manual one-/bi-dimensional measurements versus semi-automatically derived one-/bi-dimensional and volumetric measurements for therapy response evaluation of malignant lymphoma during CT follow-up examinations in a multicenter setting.Materials and Methods: MSCT data sets of patients with malignant lymphoma were evaluated before (baseline) and after two cycles of chemotherapy (follow-up) at radiological centers of five university hospitals. The long axis diameter (LAD), the short axis diameter (SAD) and the bi-dimensional WHO of 307 target lymph nodes were measured manually and semi-automatically using dedicated software. Lymph node volumetry was performed semi-automatically only. The therapeutic response was evaluated according to lymphoma-adapted RECIST.Results: Based on a single lymph node, semi-automatically derived multidimensional parameters allowed for significantly more accurate therapy response classification than the manual or the semi-automatic unidimensional parameters. Incorrect classifications were reduced by up to 9.6 %. Compared to the manual approach, the influence of the study center on correct therapy classification is significantly less relevant when using semi-automatic measurements.Conclusion: Semi-automatic volumetry and bi-dimensional WHO significantly reduce the number of incorrectly classified lymphoma patients by approximately 9.6 % in the multicenter setting in comparison to linear parameters. Semi-automatic quantitative software tools may help to significantly reduce wrong classifications that are associated with the manual assessment approach.Key Points:• Semi-automatic volumetry and bi-dimensional WHO significantly reduce the number of incorrectly classified lymphoma patients• Manual lymph node evaluation with uni-dimensional parameters is inferior to semi-automatic analysis in a multicenter setting• Semi-automatic quantitative software tools should be introduced in clinical study evaluation.Citation Format:• Weßling J, Schülke C, Koch R et al. Therapy Response Evaluation of Malignant Lymphoma in a Multicenter Study: Comparison of Manual and Semiautomatic Measurements in CT. Fortschr Röntgenstr 2014; 186: 768 – 779
Keywords: staging; abdomen; mediastinum; thorax; computed tomography; lymphoma